Enhancing 2, 6-dichlorophenol degradation and nitrate removal in the nano-zero-valent iron (nZVI) solid-phase denitrification system. (January 2022) - Li, Mingrun; Wei, Dong; Zhang, Zhaoran; Fan, Dawei; Du, Bin; Zeng, Huiping; Li, Dong; Zhang, Jie
Abstract: Nano-zero-valent iron (nZVI), as a typical nano-material, has been recently used in wastewater treatment and combination with bioreactors. Using nZVI coupled denitrification system research the effect and influence of nZVI enhanced denitrification sludge on the degradation of toxic compounds and system performance. The nZVI coupled denitrification system showed better resistance to 2, 6-DCP impact, and the concentrations of effluent NO2 − and NO3 − were below 2.0 mg/L. At the same time, the addition of nZVI enabled the denitrification system to quickly adapt to the toxic environment of 2, 6-DCP within 15 days, and the degradation efficiency of 2, 6-DCP reached 99.9%. The released SMP reduced after nZVI coupled with denitrification sludge in 2, 6-DCP environment, which could improve the effluent water quality. Nuclear magnetic resonance spectroscopy showed that the addition of nZVI would change the structure of EPS in denitrification sludge. After 90 days of operation, the dominant bacteria in the denitrifying sludge have undergone great changes. Moreover, Thauera was responsible as the dominant bacteria for degrading 2, 6-DCP in the denitrification system. The increased in the proportion of functional bacteria with nitrate_reduction, nitrogen_respiration, nitrate_respiration and nitrite_respiration in the presence of NZVI further reveals the mechanism of enhanced denitrification. Graphical abstract: Image 1 Highlights: nZVI coupled denitrification system could improve 2, 6-DCP degradation and denitrification. The release of SMP reduced in the toxic environment of denitrification sludge after nZVI addition. Dominant strains responsible for denitrification changed from Chlorobium to Thauera in Rn. Thauera were responsible for 2, 6-DCP biodegradation in nZVI coupled denitrification system.